Value chain analysis of cucumber in Arghakhanchi, Nepal - Khanal, R.; Dhakal, S. C. (Journal of Agriculture and Forestry University, 2020)
This study was done to analyze the value chain of cucumber in Arghakhanchi district during 2018. Four major cucumber producing areas, such as- Ghoche khola, Bhagwati, Baghi and Jagata were purposively selected. The value chain analysis was done with the objective to calculate benefit cost ratio in cucumber enterprise, draw the value chain map, assess the factors of production, and find out the major constraints in cucumber cultivation. A total of 64 cucumber growers and ten traders were selected using simple random sampling technique. Majority of respondents (95%) had cultivated Bhaktapur Local variety while only thirty percent of respondents cultivated hybrids. The benefit cost ratio was also higher in case of Bhaktapur Local (3.18) followed by hybrids (2.44). The most dominating marketing channel involved flow of products from farmers to retailers and then to consumers. The highest farm gate price was seen in farmers to producers’ channel. The regression estimate showed that the input variables such as- organic manure, fertilizers, materials, labor, plant protection materials had significant effects on production of cucumber. The findings showed that the major problems associated with cucumber production was diseases and insects pests attack while the major problem related to cucumber marketing was middlemen-taking higher margin. The findings also pointed out the absence of wholesalers in the value chain which somehow affected to the less production of cucumber and minimized the export opportunity.